Analisis faktor-faktor pengaruh minat mahasiswa akuntansi dalam memilih karir sebagai akuntan publik - Dzulfiadevi, Alifa; Andayani, Sari (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The aim of this research is to examine and find out the effect of Financial Appreciation, Labor Market Consideration, Working Environment, and Professional Recognition towards Accounting Students’ Interest of State Universities throughout Surabaya in Career Projection as Public Accountant. This research utilizes primary data in the form of questionnaire. The sample take on 87 respondents with sampling technique using ‘proportionate stratified random sampling’ method. The data in this research is analysed by espousing double regression analysis method whose counting is done using SPSS program. This research presents a result showing that financial appreciation, labor market consideration, working environment, and professional recognition affect the accounting students’ interest in career projection as public accountant.